EFEKTIFITAS INTERNATIONAL WHALING COMMISSION (IWC) DALAM PERBURUAN LUMBA-LUMBA ‘TAIJI DRIVE HUNT’ DI TAIJI JEPANG 2013 – 2017 - Addien Mirza Pratama; Marten Hanura (International Relations, Faculty of Social and Political Sciences, Universitas Diponegoro, 2019)
Dolphin hunting, or commonly called 'Taiji Drive Hunt' which is done massively in Taiji Region, Wakayama Prefecture, Japan occurred every year. Present the role of the IWC as an International Organization that can regulate the hunting of dolphins belonging to the cetacean’s category. Based on this background, the formulation of the problem that arises is